Upaya Peningkatan Karakter Komunikatif Melalui Model Cooperative Learning Tipe Think Pair Share Pada Pembelajaran Bahasa Indonesia Di Kelas V SDN 8 Kota Bengkulu - Putri, Tria Oktaviani; Angelia, Bertha; Rahmadilla, Nadya; Syahrani, Chaterine Dafa; Efendi, Rindang Agrianti; Agusdianita, ) Neza; Yusnia, Yusnia (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This research aims to describe the application of the TPS (Think Pair Share) type Cooperative Learning model in Indonesian language learning in class V of SDN 8, Bengkulu city. Students' self-confidence is still not optimal, students' low communication skills on rational indicators are caused by various factors such as physical appearance, self-concept, relationships with parents, relationships with peers and the use of inappropriate learning models. So it is necessary to use an appropriate learning model to encourage students' self-confidence. Having a new learning model can help increase students' self-confidence. This type of research is classroom action research (PTK), which is carried out in 2 cycles. The subjects in this research were teachers and students of class VA SDN 8 Bengkulu City. The research instruments used were observation sheets, interviews and test sheets. Data analysis techniques use data collection, data reduction, data presentation, and data verification. The results of the research show that there is an increase in students' communicative character when learning Indonesian using the TPS type Cooperative Learning model.